STUDIES ON THE EFFECT OF LEACHING ON THE QUALITY OF ICE- STORED FISH - BASU, SUBRATA; KHASIM, D IMAM (Fishery Technology, 2017)
A comparative ice storage study of milk fish ( Chanos chanos) in direct contact and out of contact (in 200 gauge polyethylene bag) with ice was taken up to assess the effect of leaching on quality of ice-stored fish. It was observed that the leaching effect was more significant on TVN and NPN than that on cc amino nitrogen components while there was very little effect on bacterial load. It is concluded that under similar conditions of icing, fish out of contact with ice will have longer shelflife and more acceptability than the fish preserved in contact with ice.